Teologi Agama-agama Tipologi Tripolar; Eksklusivisme, Inklusivisme dan Kajian Pluralisme - Ahmad zamakhsari (Departement of History and Islamic Civilization, Faculty of Ushuluddin and Adab, State Islamic University of Sultan Maulana Hasanuddin Banten, Indonesia, 2020)
Tripolar typology is one of the approaches to theology of religions that was popularized by Alan Race. This typology is used as a standard in theological studies of religions, and is still widely used in the theological discourse of religions. Tripolar typology used to map various approaches theologians and theologians non-Christian on the relation of Christianity with religions. other This mapping is based on the similarities and differences in their perspective on other religions outside Christianity. The three typologies are exclusivism, inclusivism and pluralism.Komarudin Hidayat stated that there are five typologies of religious attitudes, namely